Cardiovascular death risk reduction in type 2 diabetes patients with confirmed cardiovascular diseases - Е. V. Shlyakhto; M. V. Shestakova (Российский кардиологический журнал)
Chairs of the Workgroup: Shlyakhto E. V., Shestakova M. V.Workgroup: Arutyunov G. P., Babenko A. Yu., Barbarash O. L., Boytsov S. A., Galstyan G. R., Grineva E. N., Drapkina O. M., Duplyakov D. V., Karpov Yu. A., Koziolova N. A., Konradi A. O., Lopatin Yu. M., Martynov A. I., Nedogoda S. V., Nedoshivin A. O., Ratova L. G., Sukhareva O. Yu., Tereshchenko S. N., Khalimov Yu. Sh.